"A Space Where Queer Is Normalized": The Online World and Fanfictions as Heterotopias for WLW. Issue 13 (10th November 2022) - Llewellyn, Anna
ABSTRACT: In the current society, the online and fictional worlds are important spaces for both the identity construction and wellbeing of LGBTQ people. Connecting these spaces are fandoms (and fanfictions), which can operate as places of resistance for marginalized groups. Through the collection of survey data completed by 79 women loving women (WLW), this study therefore asks, in what ways does the online world, particularly in relation to fandoms, open up spaces for WLW. Employing a Foucauldian analysis, findings suggest communities online are crucial for affirmative support, and fanfictions are places where queerness is normalized. As such, through the displacement of time and space, online spaces (and particularly fanfictions) operate as heterotopias that significantly disrupt normative societal discourses. Accordingly, empathetic communities and the normal queer are notably absent from many WLW's physical worlds. However, caution is urged as these results are less clear for women of color.